Environmental and Energetic Performance of Crematorium Plants - Beatrice Marchi; Gioacchino Nardin; Anna Barazzutti; Fabrizio Giust (Chemical Engineering Transactions, 2023)
In recent years, in Italy, the use of cremation has grown considerably, consequently, the demand for new facilities in the area has also increased. However, the installation of new plants is often hindered by environmental associations who fear the environmental impacts of the crematoria. Scientific memoirs relating to the environmental aspects of this activity are generally intended for specific conferences, regulation also may vary from region to region. It is necessary to exercise transparency and comparison about the polluting emissions of other environmentally relevant activities. The present paper wants to make available a document with a high technical and scientific profile, which provides a methodological framework for assessing the impacts of crematoriums. To support the analysis experimental surveys on pollutant emissions, their local impact and compliance with current regulations are reported. In addition, the memorandum presents a feasibility project for the crematorium temple of Gemona del Friuli (Udine - Italy). The project wants to achieve two energy and environmental objectives, based on the thermal recovery of the energies generated by the combustion of the wooden coffin and the used fuel, aiming at the minimization of the impact. The first target is to make the crematorium independent from external energy networks (off-grid), while the second is to supply a district heating service for some users operating at short distances (i.e., two schools, a gym, and a swimming pool). From the environmental point of view, we reduce the carbon footprint of the activity and harmful emissions.